2022
DOI: 10.3390/su14148834
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Effects of Different Simulated Environmental Conditions and Hybridization Processes on the Mechanical Behavior of Different FRP Bars

Abstract: When it comes to sustainability, steel rebar corrosion has always been a big issue, especially when they are exposed to harsh environmental conditions, such as marine and coastal environments. Moreover, the steel industry is to blame for being one of the largest producers of carbon in the world. To supplant this material, utilizing fiber-reinforced polymer (FRP) and hybrid FRP bars as a reinforcement in concrete elements is proposed because of their appropriate mechanical behavior, such as their durability, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
0
1
0
Order By: Relevance
“…Uses of the basalt-reinforced polymer matrix include the strengthening of concrete structures [128]. A comprehensive review of the effects of different simulated environmental conditions and hybridization processes on the mechanical behavior of different FRP bars was given by Mirdarsoltany et al [129].…”
Section: Categorymentioning
confidence: 99%
“…Uses of the basalt-reinforced polymer matrix include the strengthening of concrete structures [128]. A comprehensive review of the effects of different simulated environmental conditions and hybridization processes on the mechanical behavior of different FRP bars was given by Mirdarsoltany et al [129].…”
Section: Categorymentioning
confidence: 99%
“…To connect to other structure members, anchorages are used for FRP tendons/cables. A large number of tests on anchorage systems of FRP tendons have been conducted [ 1 , 3 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The commonly used anchoring methods for FRP tendons mainly include bonded anchoring, mechanical anchoring, and composite anchoring [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers pointed out the safety problems associated with the use of seawater in reinforced concrete (RC) structures, since the existence of chlorides in seawater can lead to the corrosion of steel rebars, further reducing the bearing capacity of RC structures [24,25]. Recently, a few researchers have been studying the mechanical performance of fiber-reinforced polymer (FRP)-reinforced SSC [26][27][28] due to the anti-corrosion of FRP which can be an alternative to steel reinforcement [29]. Based on life cycle cost analysis (LCCA), Younis et al [30] found that the total cost of FRP-reinforced seawater concrete can be reduced by 50% compared to steel-reinforced ordinary concrete based on a 100-year study period.…”
Section: Introductionmentioning
confidence: 99%